Para diplomacia en las relaciones internacionales del Ecuador entre los años 2007 – 2013. Estudio de caso: las relaciones internacionales del Municipio del Distrito Metropolitano de Quito a partir de los intercambios de cooperación técnica con los miembros de la Unión de Ciudades Capitales Iberoamericanas (UCCI) - Rodríguez Vizcaíno, Adriana de los Ángeles (2016)
The society connections in the XXI Century in social, political, economic or cultural field have facilitated the emergence of new actors in international relations. Transnational corporations, international organizations, social movements or subversive movements are interconnected to generate links from which to obtain mutual benefits. One of the actors who has emerged as relevant in this new international arena are the cities like non central governments who have been listed as paradiplomatic actors of international relations. Now, how can we explain "paradiplomacy "? It is a conceptual approach that guides the interpretation regarding international performance of local governments to describe the implementation of its foreign policy based on decentralization and contextualized in new forms of governance. The paradiplimacy also is a socio- political and governance dynamic that develops in a system with rules and spheres of power distributed among authorities and institutions within a perspective compensation "Co". This modern form of governance moves between overlapping polarities like fragmentation and integration generating new identities with multiple loyalties. Therefore, in this new scenario the states do not dominate world politics nor force remains an effective instrument for implementing this policy and the new players in this new international situation define their topics interest without focusing on defaults established between policy high or low. This being the international situation what about Ecuador local governments? Answering this question involves analyzing the international relations of the capital, from the perspective of technical cooperation and if their actions determine somehow the central government. Management instruments such as Ecuador Political Constitution, National Plan of Good Living (PNBV), National Foreign Policy Plan 2006-2020 (PLANEX), Code of Planning and Public Finance (COPLAFIN), Territorial Organization, Autonomy and Decentralization Organic Code (COOTAD) as well as the actions of national institutions responsible for international relations of Ecuador like the Ministry of Foreign Affairs and Human Mobility and the Technical Secretariat for International Cooperation in accordance with the management of the Municipality of Quito as a member of the Union of Latin American Capital Cities (UCCI) in the fields of Culture, Tourism and Security; throw that non-central governments (read Municipality of Quito) as paradigmatic actors of international relations do not affect the decisions of the central government at the level of foreign policy.